Clinical analysis of 49 cases of coronavirus disease 2019 in Shiyan, Hubei Province - ZHAO Qin; ZHAO Qin; LEI Xu; LIU Long; ZHAN Guoqing; LI Rugui; LI Jinke; LI Fang; DU Weixing; LI Jian; YANG Jing; TAN Huabing (Di-san junyi daxue xuebao, 2020)
Objective To analyze the clinical characteristics of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in Shiyan, Hubei Province, and to compare the features with those of the recent treatment of influenza. Methods Forty-nine diagnosed COVID-19 patients admitted to the People's Hospital of Shiyan City from January 23 to February 9, 2020 were recruited in this study. Their clinical manifestations, epidemiological history, results of laboratory tests, and images of multi-slice CT (MSCT) examination were collected and analyzed, and the results were compared with the features of 31 cases of influenza virus infection (12 cases, accompanying pneumonia) during the same period. Results ① Fever and body temperature: Fever was the main complaint of the COVID-19 patients (87.76%), and the rate was significant lower than the influenza group (96.77%, P < 0.05). The COVID-19 group had low fever (22 cases) and moderate fever (21 cases) which were mainly different from those with moderate fever (12 cases) and high fever (18 cases) in the influenza group (P < 0.05). ② Cough and sputum: The incidence of cough and sputum was 65.31% in the COVID-19 group, which was significantly lower than that of the influenza group (93.55%, P < 0.01). ③ Sneezing and rhinorrhea: The incidence in the COVID-19 group was 2.04%, obviously lower than that of the influenza group (96.77%, P < 0.001). ④ Shortness of breath and chest tightness: The incidence was 12.24% in the COVID-19 group, and 29.03% in the influenza group (P < 0.05). ⑤ Fatigue and anorexia: The incidence rate was 34.69% in COVID-19 group, significantly higher than that of the influenza group (6.45%, P < 0.01). ⑥ Diarrhea: The incidence rate was 6.12% in the COVID-19 group, and no case was seen in the influenza group. ⑦ WBC count: The COVID-19 patients having a lower WBC count accounted for 77.55%, which was lower than the health control but higher than that of the influenza group (16.13%, P < 0.01). ⑧ Lymphocyte count: 38.78% COVID-19 patients had a lower lymphocyte ratio, but only 6.45% in the influenza group (P < 0.01). ⑨ Multi-slice CT (MSCT): All COVID-19 patients underwent 1 to 3 times of MSCT examination, and typical imaging features (bilateral lesions) were found in 91.84% patients. ⑩ Nucleic acid test: 77.55% patients were positive in the first time, 89.80% was in the second, 97.96% in the third, and 100% in the fourth. Conclusion Compared with influenza, COVID-19 are characterized by mainly low to moderate fever, rare chills, dry cough and sputum, very rear sneezing and runny nose, decreased WBC count, and not higher incidence of lymphocyte decline. The diagnosis needs based on the combination of clinical manifestation, epidemiological data, nucleic acid test and MSCT findings.